2013
DOI: 10.1159/000356388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TNF Haplotypes in the Physical Course of Acne Vulgaris

Abstract: Background: The role of single-nucleotide polymorphisms (SNPs) of the TNF gene in acne vulgaris remains controversial. Methods: Genomic DNA was isolated from 185 patients with acne vulgaris and 165 healthy controls. SNPs at positions -376, -308 and -238 of the promoter region of TNF were defined. Results: The frequency of the GAG haplotype was greater among patients (16.8%) than among controls with borderline significance (9.7%, p = 0.059). Male carriers of haplotypes other than GGG presented acne vulgaris at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
1
24
1
Order By: Relevance
“…Investigations about the association of TNF α polymorphisms and acne are limited in number . In our study, we did not find an association of TNF α‐308 G>A and IL1 β‐511 C<T genetic polymorphisms with acne and acne severity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Investigations about the association of TNF α polymorphisms and acne are limited in number . In our study, we did not find an association of TNF α‐308 G>A and IL1 β‐511 C<T genetic polymorphisms with acne and acne severity.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, female patients in Hungarian and Romanian population and male patients in Sicilian population showed significant difference for polymorphic variants. Investigations from different ethnic regions such as Saudi Arabia and Pakistan and three meta‐analyses which also included Chinese and Greek participants suggested that the ‐308 G/A polymorphism in the TNF α gene involves in acne risk . Among meta‐analyses, Li et al declared that TNF α‐308 AA genotype is significantly associated with acne severity and male acne patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Grech et al . investigated three SNPs (‐376, ‐308 and ‐238) of the TNF gene in a white population with fair skin . The study established that the GAG haplotype was associated with an increased risk of acne at a later age compared with the GGG haplotype, which influenced an earlier onset of the disease in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Following detailed evaluation, two studies were excluded owing to their lack of genotype frequency data. Finally, four case-control studies assessing the association between the TNF-α 308G/A polymorphism and PCOS risk published between 1999 and 2014 (Milner et al, 1999;Vural et al, 2010;Deepika et al, 2013;Grech et al, 2014), and comprising 503 PCOS cases and 649 controls were included in the meta-analysis (baseline data and other details are shown in Table 1). The distribution of genotypes in the control groups was consistent with HWE in all but one of the studies (Deepika et al, 2013).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%